COMPOSITION OF BIOGAS IN A MEDIUM-SIZED LANDFILL: TEMPORAL ANALYSIS - Boarati, Sandra Rodrigues Sarro [UNESP]; de CASTRO, Marcus Cesar Avezum Alves [UNESP] (UNESP - Universidade Estadual Paulista, 2024)
Biogas generated in landfills is a renewable source and can be used to generate heat or electricity with a high energy percentage bringing economic benefits combined with environmental sanitation. The objective of this work was to analyze the composition of the generated biogas, relating it to the grounding time of the solid residues disposed in the sanitary landfill of Rio Claro/SP. A comparative analysis of temperature, influence of rainfall on the flow and concentration of methane (CH4) and carbon dioxide (CO2) of the biogas in the period of 18 months was carried out. It is concluded that biogas production was lower in older areas. The influence of precipitation on biogas generation was more pronounced in cells with less disposal time in the landfill. The increasing values of biogas flow indicate an increase in anaerobic biological activity.
COMPOSIÇÃO DO BIOGÁS EM ATERRO SANITÁRIO DE PORTE MÉDIO: ANÁLISE TEMPORAL
Keywords: Biogas; Municipal Solid Waste; Sustainability